Do We Need a Software Czar? - Grier, David Alan (Computer (00189162), 2015)
We need to temper authoritarian leadership with the insights of individual programmers. The Web extra at http://youtu.be/TvJQ9Zt2BUs is an audio recording of author David Alan Grier expanding on his Errant Hashtag column, in which he talks about how we need to temper authoritarian leadership with the insights of individual programmers.